Cognitive impairment in Chinese patients with cervical dystonia - Liu, Kuncheng; Hou, Yanbing; Ou, Ruwei; Yang, Tianmi; Yang, Jing; Song, Wei; Zhao, Bi; Shang, Huifang (Frontiers in Neurology, 2022)
Objective: Cognitive impairment (CI) in patients with cervical dystonia (CD) has been reported by many studies but with inconsistent findings. We investigated the prevalence, characteristics, and clinical factors related to CI in Chinese patients with CD. Methods: Sixty-eight CD patients and 68 healthy controls (HCs) were included in the study. Demographic and clinical data were investigated. A logistic regression analysis was conducted to discriminate the clinical factors associated with CI in CD. A cluster analysis was performed to explore the different characteristics within the group of CD patients with CI. Results: We found that 42 (61.76%) CD patients had CI. The most frequent CI domain was visuospatial function (39.71%), followed by memory (38.24%), attention/working memory (29.41%), language (25.00%), and executive function (23.53%). CD patients with CI were older, less educated, had an older age of onset, more severe motor symptoms and disability, and experienced more pain than CD patients without CI. The presence of CI in CD was associated with less education (OR=0.802, p=0.034) and a higher Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) severity subscore (OR=1.305, p=0.001). The cluster analysis identified two different subgroups of patients, one with relatively mild cognitive impairment and the other with relatively severe cognitive impairment. Conclusions: CI is relatively common in Chinese patients with CD, with the most common CI domain of visuospatial function. In the present study, CI in CD was associated with less education and more severe motor symptoms, and patients with CI may be further divided into two subgroups based on different extent and domain of cognitive decline.